Peran Pivot Hooks dalam Peningkatan Kapasitas Lentur pada Balok Beton Bertulang Bambu - Ummati, Alfinna Mahya; Michael, Michael; Sarassantika, I Putu Ellsa; Fanna, Gibral Tariq; Syuhada, Syahidus; Bayzoni, Bayzoni; Nasution, Ade Prayoga (MEDIA KOMUNIKASI TEKNIK SIPIL, 2023)
Some researcher missed the role of hooks in their bamboo reinforcement. Consequently, the bamboo reinforcement and concrete used to have slip and failure to composited, this make the concrete and bamboo working independently to sustain the given loading and the bond failure become the main issue than the beam failure. This research studied about the role of the pivot hooks that capable to enhance the loading capacity higher than the beams without the pivot hooks. Experimental test performed in order to identify the effect of the pivot hooks presence which added to the flexural reinforcement which made by bamboo materials to avoid the bond slip failure that mostly occur in the bamboo reinforced concrete beams. The experimental test which verified by the numerical analysis by FEA NX commercial software proof that the pivot hooks are able to increase the loading capacity of a concrete beam 33% - 40% higher than the bamboo reinforcement without the pivot hooks. Architectural façade and budget efficiency caused the bamboo become unavoidable material in construction, by adding the structure modification such as the pivot hooks for the bamboo reinforcement, the failure can be reduced, then the entanglement of bamboo in construction become more functional.